2015
DOI: 10.3748/wjg.v21.i25.7718
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective effect ofGeranium schiedeanumagainst ethanol toxicity during liver regeneration

Abstract: The administered extract showed a hepatoprotective effect, limiting the EtOH-induced hepatotoxic effects. This effect can be related to modulating oxido-reduction processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…This might have happened because the ethanol metabolism increased the NADH/NAD + ratio changing the redox state balance in hepatocytes (Zakhari 2006), which mobilizes fatty acids for accumulation instead oxidation, resulting on fatty liver condition that lead to impairments of others metabolic pathways increasing the serum triglycerides. Thus, beyond antioxidant property of coconut water, ascorbic and caff eic acid modulating positively triglycerides levels (Madrigal-Santillán et al 2015), impairment on glucose and lipid metabolism could be improved by glucose, ascorbic and caff eic acid present in coconut water, leading to reduction on triglyceride serum content (Braun et al 1996, Jung et al 2006). …”
Section: Resultsmentioning
confidence: 99%
“…This might have happened because the ethanol metabolism increased the NADH/NAD + ratio changing the redox state balance in hepatocytes (Zakhari 2006), which mobilizes fatty acids for accumulation instead oxidation, resulting on fatty liver condition that lead to impairments of others metabolic pathways increasing the serum triglycerides. Thus, beyond antioxidant property of coconut water, ascorbic and caff eic acid modulating positively triglycerides levels (Madrigal-Santillán et al 2015), impairment on glucose and lipid metabolism could be improved by glucose, ascorbic and caff eic acid present in coconut water, leading to reduction on triglyceride serum content (Braun et al 1996, Jung et al 2006). …”
Section: Resultsmentioning
confidence: 99%
“…Studies also showed that Monolluma quadrangula (Forssk.) Plowes, Geranium schiedeanum Schltdl., and Phyllanthus emblica L. are also effective in this respect (Ibrahim et al, 2015;Madrigal-Santillán et al, 2015;Chaphalkar et al, 2017). Recently a number of reviews have been published on the topic (Guan et al, 2018;Singh et al, 2018).…”
Section: Preclinical and Clinical Research Based On Ethnopharmacologimentioning
confidence: 99%
“…The authors reported that liver regeneration was delayed after PH in the absence of Nrf-2, suggesting that the activation of this transcriptional factor could improve liver regeneration in patients with acute or chronic lesion. Madrigal-Santillán et al [ 31 ] reported the hepatoprotector effect of Geranium schiedeanum in the inhibition caused by ethanol after PH, suggesting that this protection is due both to the trapping effect of the free radicals possessed by G. schiedeanum and to the regulation of Nrf-2, concluding that Nrf-2 protects the regenerating liver from ethanol-related damage.…”
Section: Nrf-2 and Liver Regenerationmentioning
confidence: 99%